Facile synthesis of flake‐like MnO2/CNFs catalysts and their activity in low‐temperature NO reduction with NH3. (1st January 2017) - Chen, Jian; Zheng, Yuying; Cai, Weilong; Zou, Haiqiang; Zheng, Weijie; Zhang, Yanbing; Chen, Xuehong; Fu, Binbin
Abstract : A series of MnO2 /carbon nanofibres (CNFs) catalysts were prepared by a facile co‐precipitation method for low‐temperature selective catalytic reduction (SCR) of NO with NH3 . These catalysts were characterised by the techniques of specific surface area measurements (BET), X‐ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X‐ray photoelectron spectroscopy (XPS) and H2 temperature‐programmed reduction (H2 ‐TPR). The XRD, FESEM and TEM results showed that the CNFs were surrounded by MnO2 nanoflakes. Compared with the MnO x /CNFs catalyst prepared by the wet impregnation method, the MnO2 /CNFs catalysts exhibited better low‐temperature SCR activity at low temperature. The XPS results indicated that a higher concentration of Mn 4+ and more surface oxygen species exited on the surface for 8% MnO2 /CNFs catalyst. The H2 ‐TPR profiles displayed that the 8% MnO2 /CNFs catalyst presented stronger low‐temperature reducibility than the MnO x /CNFs catalyst. Based on the abovementioned favourable properties, the 8% MnO2 /CNFs catalyst has an excellent performance in the low‐temperature SCR of NO with NH3 .